Political state and the dilemma of dignity, equality and freedom: Evidence from a sovereign state - Khan, Md. Mahfuzur Rahman (Dynamics of Politics and Democracy, 2021)
Purpose: This study discusses the idea of political redefinition and its connection to dignity, freedom and equality in a sovereign state. This article concludes by briefly touching on some serious issues about sovereign communities that arise as a result of the fundamental dignity, freedom, and equality ideals of the sovereign state. Research methodology: The author decided to conduct theoretical research in a qualitative format using conceptual analysis as well as critical and rational argumentation. A deductive approach is used in reaching a prior opinion. Results: The sovereign state itself became the judge and restricted human dignity, equality and the freedom to contract by forcing citizens to make transfers they did not consent to and prohibiting certain private transactions on the sole pretext. Limitations: There are shortcomings in theoretical research, as the author used a deductive approach to conclude. Contribution: This study conceptualizes the proponents of a sovereign state to be drawn into the dilemma of dignity, freedom and equality.